Traceability and failure consequences of natural gas explosion accidents based on key investigation technology. (September 2022) - Hu, Qianran; Zhang, Qi; Yuan, Mengqi; Qian, Xinming; Li, Mingzhi; Wu, Hao; Shen, Xingyu; Liang, Yiming
Highlights: A key investigation technology is developed for large-scale gas explosion accidents. The cause of the accident is determined based on object failure analysis. The entire process of accident is truly restored by numerical methods. The shock wave overpressure and high-speed airflow are the main hazard factors. Abstract: In recent years, there have been frequent gas explosion accidents in China. On October 21, 2021, a gas explosion occurred in Northeast China, resulting in 5 deaths and 52 injuries. To further improve accident investigation theories and methods, with the help of key accident investigation technologies, this study carried out traceability, investigation, and failure analyses regarding the above-mentioned typical natural gas leakage and explosion. The investigation showed that natural gas leaked from a gas pipeline almost filled the entire accident building within 3 h and 25 min and the gas concentration was between 7 and 9 vol% before the accident. An electric spark generated by the action button of a refrigerator was the key ignition factor. The peak explosion overpressure near the ignition was 57 kPa and peak temperature reached 1620 K. The outdoor explosion venting overpressure less than 30 kPa, but the venting airflow velocity exceeded 90 m/s, with many items and fragments thrown outside, resulting in three deaths and many injuries. In addition, based on calculations of gas concentration and diffusion volume, the total amount of natural gas leakage in the accident reached 150 m 3 . Based on the TNT equivalent method, the TNT explosion equivalent of the accident was 80 kg. These investigation results ideally restored the entire explosion accident process and the research methods and failure analysis ideas developed here will provide scientific guidance for the investigation of such accidents and evaluation of explosion effects.